Pengembangan Media Pembelajaran Modul Elektronik (E-Modul) Menggunakan Google Site pada Mata Pelajaran TIK di MA Al Fattahiyyah - Fika Nailul Muna; Fahrur Rozi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Electronic modules (E-modules) are a set of digital learning media that are systematically designed to support independent learning. E-modules can be used as a complement to teaching materials in learning activities, especially in the application of electronic-based media. The purpose of this study is to develop e-module learning media in Google Site-based ICT subjects that are suitable for use at MA Al Fattahiyyah Tulungagung. This research uses a research and development approach (Research and Development) with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model. The material developed in the e-module is adjusted to the MA Al Fattahiyyah class X syllabus, especially the material "Computer Network". The subjects of this study include 1 lecturer of media experts, 1 teacher of ICT subjects as material experts, and students of class X of MA Al Fattahiyyah. The research instrument consisted of a media feasibility assessment sheet, a material assessment sheet, and a questionnaire of students' responses to the use of e-modules. The results of the study showed that the e-module was declared suitable for use as a teaching material with scores from media experts of 87%, material experts of 93%, and the results of user trials (students) in small and large groups showed excellent results. Thus, Google Site-based e-module learning media on Computer Network materials at MA Al Fattahiyyah is included in the category of "Very Feasible" and can be used to support a more interactive and effective learning process for students.